Creating a Perioperative Glycemic Control Program - Sara M. Alexanian; Marie E. McDonnell; Shamsuddin Akhtar (Anesthesiology Research and Practice)
Hyperglycemia in the surgical population is a recognized risk factor for postoperative complications; however, there is little literature to date regarding the management of hyperglycemia in the perioperative period. Here, we detail the strategies that our institutions have employed to identify and treat hyperglycemia in patients with diabetes who present for surgery. Our approach focuses on the recognition of hyperglycemia and metabolic abnormalities, control of glucose levels via insulin infusion when needed, monitoring for hypoglycemia and a comprehensive multidisciplinary approach that provides standardized recommendations for patients at all points in care as they transition from the preoperative clinic into the operating room, and then into the hospital.